SELECTIVE LASER TRABECULOPLASTY AS A VALUEABLE MODALITY OF TREATMENT IN OPEN ANGLE GLAUCOMA PATIENT: Oral Presentation - Observational Study - Ophthalmologist - TRIANGGADEWI, DYAH PURWITA; Umbara, Sonie; Rifada, R Maula; Gustianty, Elsa; Prahasta, Andika (Majalah Oftalmologi Indonesia, 2023)
Introduction & ObjectivesSelective Laser Trabeculoplasty (SLT) has became an established treatment to lower intraocularpressure (IOP) for open angle glaucoma (OAG) and ocular hypertension. The aim of this study was toevaluate IOP lowering effect of SLT and correlate its laser parameter to the successful rate in OAG. MethodsThis is a prospective study of seventeen eyes OAG patients in Cicendo Eye Hospital from 1stNovember 2022 to 31th December 2022. SLT performed once in OAG with uncontrolled IOP (IOP >21 mmHg). Outcome measured were IOP at post laser, 1week , 1 month, and 2 months of follow upafter SLT. Successful criteria determined as greater than 20% IOP reduction. Correlation betweensetting operational of SLT and primary outcome were measured. Student’s t-test (two-tailed,dependent) has been used to find the significance of study parameters. ResultsA total 17 eyes underwent SLT. Mean baseline IOP was 21,12 ? 4,0 mmHg. IOP was significantlydecreased from baseline post laser 18,06 ? 3,17 mmHg; at 1 week 17,06 ? 3,25 mmHg; 1 month15,53 ? 4,52 mmHg; and at 2 month follow up 15,47 ? 4,02 mmHg (p<0,001). The successful rate ofSLT after two months follow up from this study were 76,5% samples (13 eyes). Mean of total laserenergy was 75,6 ? 16,8 mJ. There was correlation between total laser energy with percentage of 1month IOP reduction (coefficient : 0,470 (p<0,029)). ConclusionSLT is effective and safe for reducing IOP in open angle glaucoma patient.